EVALUASI MATERIAL PEMBENTUK ASAM TAMBANG PADA PENGELOLAAN LAHAN REVEGETASI DI AREA BEKAS PENAMBANGAN BATUBARA - Herniwanti Herniwanti; Udiansyah Udiansyah; Bambang Joko Priatmadi; Emmi Winarni (EnviroScienteae, 2012)
The purposes of the research were to find out: 1) The acid mine drainage contents, and their relationship with the growth of plants on the revegetation land; 2) the success level of revegetation of ex-mining land by estimating the parameters of plant growth, runoff water and animal population. The result indicated that the parameter of plant growth on the vegetation land increased according to the planting year and 60% growing comparison with Acacia mangiun species in Forest Plantation Industry the low growings influenced by the acid mine drainage contents result variance of PAF LC 1- PAF Category and the water quality still below by goverment requlation as PerGub Kalsel No.36 year 2008 for specification for mining waste water. Animal population have positife growing in the area by step depend on revegetation growing . There was relationship between plant growth, acid mine drainage and water quality, but in 2006 the plant growth was disturbed because it contained high acid mine drainage and water quality exceeding threshold.